Pelaksanaan Strategi Marketing Mix Yang Efektif Dalam Usaha Meningkatkan Kinerja Pemasaran Masa Pandemi Covid-19 Pada Cv. Sarjana Tembakau Malang - Jaelani Chafidz Nur Shihab; Nur Hidayati; Muhammad Ridwan Basalama (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to determine the implementation of an effective marketing mix strategy to improve marketing performance that focuses on sales growth. Research locations at the company CV. Sarjana Tembakau Malang. This research is a qualitative descriptive study. Data collection techniques using interviews, observation, and documentation study. The data analysis technique of this research uses two analytical approaches, namely quantitative descriptive analysis and qualitative descriptive analysis. Based on the results of data analysis, the marketing mix strategy is a combination of the marketing mix consisting of products, prices, distribution channels, and promotions. The strategy was carried out by CV. Sarjana Tembakau Malang looks at marketing effectiveness points to provide the accuracy of marketing strategies implemented by the company. Thus, it is important to improve marketing performance, namely the company's sales growth targetKeywords: Marketing Mix Strategy, Marketing Effectiveness, Marketing Performance